Nitrogen and molybdenum fertilization in dry bean under irrigated conditions - Fullin, Eli Antonio; Zangrande, Moema Bachour; Lani, José Antônio; Mendonça, Luciano Furtado de; Filho, Nilton Dessaune (Pesquisa Agropecuaria Brasileira, 1999)
This field experiment was conducted to evaluate the effect of application of nitrogen (N) associated or not with molibdenum (Mo) application to the dry bean cultivar Goytacazes under irrigation. The soil was a cohesive Dark Yellow latosol (Oxisol) at Linhares, ES, Brazil. A randomized complete blocks design with three replications was used. Nitrogen rates as urea, ranged from 0 to 10 kg/ha at planting and 0 to 40 kg/ha sidressed. Molibdenum was mixed with the seeds and applied by foliar spraying at rates of 0 and 20 kg/ha as ammonium molybdate. One additional treatment with 10 kg/ha of N and 40 kg/ha of FTE BR 9 at planting plus 40 kg/ha of N sidressed was used. The highest grain yield was recorded with the application of 10 kg/ha and 40 kg/ha of N at planting and sidressed, respectively, associated to 20 kg/ha of Mo by foliar spraying.